Colour and Morphometric Variation of Donacid Bivalves from Nepa Beach, Madura Island, Indonesia - Ambarwati, Reni; Faizah, Ulfi (Biosaintifika: Journal of Biology & Biology Education, 2017)
Donacid bivalves vary in colour, pattern, and the shape of the shells. A population of donacid bivalves had been found in the northern shore of Madura Island, Indonesia. This study aimed to identify the donacids found in northern shore of Madura Island as well as to describe their variation on morphometric and morphological characters. Colour and pattern of 215 shells were observed and carefully photographed. Morphometric of the shells including the shell height, shell length, shell width, dorsal length, and umbo-margin length were measured and then their patterns were analyzed using regression analysis. The results revealed that there were two species of donacid bivalves in Nepa Beach, namely Donax cuneata and Donax faba with different morphological characteristics, including twelve different patterns and colours of the shells. These variations were described completely in this paper. This study contributes to the research on bivalve taxonomy, and is useful for the identification of donacid bivalves based on morphological characteristics.